UJI ORGANOLEPTIK KESEGARAN IKAN LAYANG (Decapterus, sp) SELAMA PENANGANAN SUHU DINGIN - Ainul Mardiah; Indira Karina; Eddwina Aidila Fitria (Universitas Muara Bungo, 2022)
Handling the layang fish (Decapterus sp) cold chain is an effort to maintain the freshness of fish until it reaches consumers in a fresh condition. Added ice flakes are the method for applying low temperatures in storage so that fish are durable and long-lasting. The purpose of this study was to analyze the freshness level of layang fish after being stored for 0, 2, 4, and 6 hours. The study used an experimental method with four treatments and three replications. Fish samples were taken directly from Tempat Pelelangan Ikan (TPI) Bungus, Padang, and transported to the laboratory using a cold box. On arrival at the laboratory, the fish samples were separated into several cold boxes which had been given ice flakes with the ratio of fish to ice 1:1. Then, the organoleptic test was carried out using 25 semi-trained panelists. The organoleptic parameters were eyes, gills, mucus, fish cutlet, odor, and texture of layang fish. The results showed that chilled storage for 2-4 hours found that layang fish was still categorized as fresh and received a score of 6.00 – 7.48 from the panelists, meaning that fish was highly favored by consumers. After 6 hours of chilled storage, the quality of fish began to decline with an average score ranging from 4.72-5.20 with the characteristics of fish eyes turning red and the fish flesh becoming mushy. Handling chilled temperatures is necessary to maintain the quality and freshness of layang fish. The best-chilled storage temperature was about 2-4 hours.